ANALISIS EFISIENSI RELATIF PERBANKAN CAMPURAN (JOINT VENTURE BANKS) DI INDONESIA TAHUN 2007 -2010 DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Dian Pramana; Nugroho SBM (Universitas Diponegoro, 2012)
Banks play an important role in economic development not only in Indonesia, in many industrialized countries, banking is needed for the economic development it is also a financial intermediary. But the banking business also can not be separated from a variety of risks in running its operations. To minimize the risk, the banks need to act rationally in the sense of attention to efficiency issues. If viewed from the general banking performance indicators in Indonesia, Joint Venture Banks is the most inefficient. Therefore in this study will analyze the efficiency of Joint Venture banks in Indonesia with a methods Data Envelopment Analysis (DEA), and the sampled put 15 Joint Venture banks in Indonesia in 2007-2010. The variables used were four input variable (Labor Expenses, Fixed Assets, Total Deposits, and General and Administrative Expenses) and four output variables (Total Credit, Cash, Other Operating Income, and Money Instruments). The study results of the 15 joint venture banks in 2007 there were three banks that are inefficient (not yet reached 100%), in 2008 there were six banks that are inefficient, in 2009 and 2010 there were two banks that are not efficient. The cause of inefficiency, especially by the using of input resources that not proportionate.